Time series modelling : design, testing and optimisation using genetic algorithms - Ting, Hoe Ming. (2009)
This project investigates a methodology of using Genetic Algorithm for time series modelling. The importance of time series modelling and growing popularity of GA in model optimisation forms the main thrust for the study.